Pengungkit Kredibilitas dan Brand Trust pada Website Bank Digital di Indonesia - Riadi, Ari; Widiatmoko Soewardikoen, Didit; Swasty, Wirania (Faculty of Humanities and Creative Industries, Maranatha Christian University (formerly Faculty of Fine Arts and Design), 2023)
Digital banking is the newest business model in the banking industry. These industries that implement this financial technology system, consumers are still hesitant and afraid to use digital banks because of the high number of cyber-attacks. In this case, digital banks need to build brand trust to gain the trust of their target consumers. The website is an effective communication channel to build brand trust in consumers. Each bank has a variety of digital communication strategies in adding aspects that are presented on the website. This study aims to analyze and review the burden of responsibility for digital bank websites in Indonesia. Purposively selected three digital bank brands: Neobank, Jenius, and Blu. Data were collected by observation and documentation methods on digital bank websites, then analyzed using comparative analysis and content analysis. The study results mention the content of relevant visual communication elements, consistent use of visual identity, and completeness of the information presented on digital bank brand websites to establish brand trust. Through this research, it is expected that industries that apply financial technology can optimize the website as a medium for forming brand trust and basic considerations to determine the company's competitive advantage strategy.